International Cooperation and Integration Directions of Uzbekistan's Higher Education - Umarova Feruza Roziboyevna; Rakhimova Saida Durdiyevna (Scientific Trends, 2025)
This article analyzes the process of integration of the higher education system of the Republic of Uzbekistan into the international educational space, forms of international cooperation, existing problems and promising directions. Also, important aspects of the development of the higher education system of Uzbekistan based on world best practices are highlighted.
Keywords: Higher education, international cooperation, integration, academic mobility, international ratings, quality of education.